The Mediator Role of Perceived Stress in the Relationship between Academic Stress and Depressive Symptoms among E-learning Students with Visual Impairments. (March 2017) - Lee, Soon Min; Oh, Yunjin
Introduction: This study examined a mediator role of perceived stress on the prediction of the effects of academic stress on depressive symptoms among e-learning students with visual impairments. Methods: A convenience sample for this study was collected for three weeks from November to December in 2012 among students with visual impairments attending a Korean cyberuniversity in Seoul. A total of 103 students with visual impairments completed the survey via e-mail or telephone, with an overall response rate of 72.54%. Results: The present study demonstrated that perceived stress fully mediated the effect of academic stress on depressive symptoms. Academic stress was significantly associated with perceived stress and depressive symptoms, and perceived stress was significantly associated with depressive symptoms. However, the association between academic stress and depressive symptoms was no longer significant when perceived stress was included as a mediator. Discussion: This finding supports the full mediation model by demonstrating that academic stress indirectly influences depressive symptoms through perceived stress, and by highlighting the important contribution of perceptions of stressors. Implications for practitioners: Cyberuniversities, professors, and disability services offices need to identify and assess what academic resources are available. To improve the accessibility of e-learning materials and settings, reasonable accommodations in e-learning settings and special online assistance services should be provided. A precollege orientation program and a training program for better adaptation and usage of the e-learning materials and technologies are needed. Senior students' successful experiences and know-how should be shared among students with visual impairments. Psychological counseling services for students who have a high level of depressive symptoms should be provided.